BRAIN GYM DAPAT MENINGKATKAN KONSENTRASI BELAJAR MAHASISWA STEI INDONESIA RAWAMANGUN JAKARTA TIMUR - Mohammad Ali; Toto Aminoto (Poltekkes Kemenkes Jakarta III, 2018)
The ability to focus on tasks / lessons is important to improve the achievement of a student.To get the results, it takes a sufficient intake of oxygen for the brain to generate energy. Oneform of effort to increase the intake of such intake is with Brain Gym. This study aims toprove the influence of Brain Gym on the concentration of students learning STEI Indonesiarawamangun East Jakarta. The benefits of this study is for physiotherapists to prove theinfluence of Brain Gym on the concentration of students learning STEI Indonesiarawamangun East Jakarta to always be able to concentrate so as to get better learningoutcomes. Sampling technique used is purposive sampling and continued with simple randomsampling. Total number of 68 students divided into study and control group participated inthis research. Statistical analysis used is paired t test and independent t test if normaldistributed. The results showed that Before Intervention produced average value equal to44.65 which means the level of concentration is moderate and after Intervention producedaverage value equal to 59.26 which means the level of concentration is quite moderate. Thecalculation results show that there is a difference between the control group and thetreatment group. The result of the calculation of the average value shows that the treatmentgroup is higher than the control group. Thus the treatment group is more effective.